3-Chloro-N′-(2-chloro-5-nitrobenzylidene)benzohydrazide - Zhen Zhang (Acta Crystallographica Section E, 2011)
The title molecule, C14H9Cl2N3O3, has an E configuration with respect to the methylidene unit. The dihedral angle between the mean planes of the two benzene rings is 12.3 (3)°. In the crystal, molecules are linked via bifurcated N—H...(O, N) hydrogen bonds into chains along [001].